Availability Analysis of GNSS Signal in High Orbit - Lu Kewen,Wang Xinlong,Shen Liangliang,Cai Yuanwen,Chen Ding (Editorial Office of Aero Weaponry, 2021)
Global navigation satellite system (GNSS) has the characteristics of strong autonomy, high real-time, high positioning accuracy and low cost, and it has been widely used by ground, low earth orbit (LEO) and medium earth orbit (MEO) users. However, in the high orbit environment, the availability of GNSS signal is greatly limited due to the earth’s blocking and the increase of signal’s transmission distance, which restricts the application and development of GNSS in the autonomous navigation of high orbit satellites. Aiming at the unknown problem of GNSS signal’s availability in high orbit, the availability of GNSS signal in high orbit is systematically analyzed from the aspects of GNSS satellite’s visibility, Doppler frequency shift and its rate of change, geometric dilution of precision, etc. Based on the characteristics of GNSS link propagation, the spatial coverage characteristics and strength distribution characteristics of GNSS signal in high orbit are analyzed, and then the visibility of GNSS satellites in high orbit is evaluated. The effects of Doppler frequency shift and its rate of change on the performance of signal acquisition and tracking are explored by using the acquisition model and the phase-locked loop model, and geometric dilution of precision of different GNSS combinations and their changes are quantitatively calculated.